'A Swarm of Sound': Audiovisual Immersion in Björk's VR Video 'Family'. Issue 1 (1st July 2022) - BRESLER, ZACK; HAWKINS, STAN
Abstract : This article explores the idea of audiovisual immersion through the portal of the virtual reality music video. Our focus falls on a close reading of Björk's video, 'Family', which addresses questions of immersion in relation to user-experience, staging, and technological innovation. This article draws on the authors' responses to the video by considering the implications of VR immersion in a new generation of music video productions. As part of the methodology on offer, a model for music analysis is devised for conceptualising virtual audiovisual space (VAVS) and the inextricable relationships between production and compositional design.